Performance Bank Islam Malaysia Berhad and Affin Holdings Berhad share price during economic and financial crisis (2007-2009) / Nurzahidah Jamaluddin - Jamaluddin, Nurzahidah (2010)
The general objective of the study is to measure the performance of BIMB (Shariah compliant stock) with Affin Holdings Berhad (non-Shariah compliant) share prices during 2007 to 2009. Does it affecting the performance of BIMB and Affin Holdings share prices?